KINERJA KOMISI PEMILIHAN UMUM DAERAH DALAM PROSES PENETAPAN DAFTAR PEMILIH TETAP (DPT) PADA PEMILIHAN KEPALA DAERAH KABUPATEN KUANTAN SINGINGI TAHUN 2011 (KASUS KELURAHAN PASAR BARU BASERAH KECAMATAN KUANTAN HILIR) - ", Idris; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
For Kuantan Singingi District, Local Elections has been started since 2006, when it was followed by four pairs of candidates. The second Elections was conducted by the Commission Elections Kuantan Singingi District in 2011. For the technical implementation of the Commission District Regency based on the Act, Government Regulation, Presidential Regulation, Regulation of the Minister, and the Commission Elections Regulation of Republic of Indonesia. The candidates contesting on the serial number is a pair H.Sukarmis and Drs.H.Zulkifli, M.Si while the number two is pair Drs.H.Mursini and Gumpita, SP, M.Sc.The purpose of this study was to determine the performance of Regional Elections Commission in process determination of the Permanent Voters List on the implementation of Local Elections in Kuantan Singingi District in 2011 in Pasar Baru Baserah Village and determine the factors that hinder performance of Regional Elections Commission in process determination of the Permanent Voters List on the implementation of Local Elections in Kuantan Singingi District in 2011 in Pasar Baru Baserah Village.Based on the research results can be some conclusions as follows: (1) Determination of the Permanent Voters List in Pasar Baru Baserah Village completely not going well, where the Regional Elections Commission as the organizers are not professional in perform activities of determining the Permanent Voters List, so disadvantaged communities, (2) Lack of socialization Regional Election Commission about the Election schedule, Election procedures, requirements to become voters and easiness choose if it is not listed in the Permanent Voters List, it adds to the complex issues in the Pasar Baru Baserah Village. (3) Problems muddle Permanent Voters List in the Pasar Baru Baserah Village is due to inputting errors defined by their weak human resources and computer technology used many heavily damaged.In order to improve the quality of Elections or Local Elections in Indonesia in the future, system uses Identity Card, Family Card as evidence for the use the right to vote of citizen voters was not enough, and should be fixed or addressed. Therefore, under the circumstances and conditions of the administration management of population is weak as it is today, issue or problem is how and who should be responsible and able to provide assurances that the person will not have more than one Identity Card or Family Card, or Identity Card and Family Card is authentic and valid.Keywords: Performance, Commission Elections Kuantan Singingi District, the Permanent Voters List.